Research progress in RBC alloimmunization - Fu, Zike; Hao, Xinxin; Gao, Wa; Wang, Quishi (Frontiers in Immunology, 2025)
Red blood cell (RBC) alloimmunization is a common and clinically significant immunological phenomenon in transfusion medicine, pregnancy management, and organ transplantation. It involves complex interactions between RBC antigens and the host immune system. Recent studies have revealed that RBCs are not merely passive immunological targets but also play more complex roles in the initiation and regulation of alloimmune responses. This review begins with the immunogenic properties of RBC antigens and systematically outlines the molecular mechanisms of alloimmunization, including T cell-dependent and-independent responses, functional differentiation of dendritic cells and marginal zone B cells, complement regulation, and multiple pathways of immune tolerance. On this basis, we highlight key factors influencing the occurrence of alloimmunization, such as antigen characteristics, recipient inflammatory status, donor RBC quality, underlying disease conditions, transfusion-related variables, and other potential mechanisms. Using sickle cell disease (SCD) and hemolytic disease of the newborn (HDFN) as representative models, we further explore the distinctive features and clinical implications of RBC alloimmunization in different disease contexts. This review aims to provide a systematic framework for understanding RBC-mediated immune responses and to establish a theoretical foundation for developing individualized immunomodulatory strategies.